Fault tolerant properties of kinematically redundant manipulators - Maciejewski, Anthony A., author; IEEE, publisher (Colorado State University. Libraries, 1990)
The dexterity of kinematically redundant manipulators has been quantified and utilized for satisfying a variety of performance criteria. In this work, the degradation of dexterity due to a joint failure is analyzed. A definition of fault tolerance based on a worst-case measure of the remaining dexterity is presented and the properties of optimal fault tolerant configurations are discussed.
Keywords: kinematics; robots